A Structural Exploration of Demi-Complementation on ADLs - Rafi, Noorbhasha; Ansari, Abu Zaid; Rao, M. Sambasiva; Monikarchana, Y.; Shujat, Faiza (Contemporary Mathematics, 2025)
On an Almost Distributive Lattice (ADL), the concept of demi-complementation is introduced. From demi-complemented ADLs, we derived some important and interesting properties. Every demi-complemented ADL is given set equivalent conditions that yields a pseudo-complemented ADL, an MS-ADL, and a pseudo-complemented lattice.